Real‐time patient experience surveys of hospitalized medical patients. Issue 4 (18th January 2016) - Indovina, Kimberly; Keniston, Angela; Reid, Mark; Sachs, Katherine; Zheng, Chi; Tong, Angie; Hernandez, Danny; Bui, Kathy; Ali, Zeinab; Nguyen, Thao; Guirguis, Helpees; Albert, Richard K.; et al.
Abstract : BACKGROUND: Real‐time feedback about patients' perceptions of the quality of the care they are receiving could provide physicians the opportunity to address concerns and improve these perceptions as they occur, but physicians rarely if ever receive feedback from patients in real time. OBJECTIVE: To evaluate if real‐time patient feedback to physicians improves patient experience. DESIGN: Prospective, randomized, quality‐improvement initiative. SETTING: University‐affiliated, public safety net hospital. PARTICIPANTS: Patients and hospitalist physicians on general internal medicine units. INTERVENTION: Real‐time daily patient feedback to providers along with provider coaching and revisits of patients not reporting optimal satisfaction with their care. MEASUREMENTS: Patient experience scores on 3 provider‐specific questions from daily surveys on all patients and Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) scores and percentiles on randomly selected patients. RESULTS: Changes in HCAHPS percentile ranks were substantial (communication from doctors: 60th percentile versus 39th, courtesy and respect of doctors: 88th percentile versus 23rd, doctors listening carefully to patients: 95th percentile versus 57th, and overall hospital rating: 87th percentile versus 6th ( P = 0.02 for overall differences in percentiles), but we found no statistically significant difference in the top box proportions for the daily surveys or the HCAHPS survey. The median [interquartile range] top box score for the overall hospital rating question on the HCAHPS survey was higher in the intervention group than in the control group (10 [9, 10] vs 9 [8, 10], P = 0.04). CONCLUSIONS: Real‐time feedback, followed by coaching and patient revisits, seem to improve patient experience. Journal of Hospital Medicine 2016;11:251–256. © 2016 Society of Hospital Medicine